Climate resilience of traditional olive-growing systems: an ethnobotanical and agro-ecological study in Khenchela, Algeria - Milek, Somia; Aziz, Nadia Nawel; Benrachou, Nora; Hacini, Nesrine; El Melki, Mohamed Nejib (Ethnobotany Research and Applications, 2026)
Background: Climate change poses significant threats to Mediterranean olive-growing systems, primarily through rising temperatures, precipitation variability, and water scarcity. The Wilaya of Khenchela in northeastern Algeria, with pronounced agroclimatic heterogeneity (annual rainfall ranging from 60 to 431 mm), offers an ideal context to assess olive system resilience under contrasting environmental constraints. Despite Algeria being the ninth largest global olive producer, systematic assessments of how genetic diversity, morphometric traits, and socio-economic factors interact to confer adaptive capacity remain scarce. Methods: A cross-sectional survey was conducted among 286 olive growers across five municipalities representing North Khenchela (NKh) and South Khenchela (SKh) agroclimatic zones. Data collection combined semi-structured questionnaires, morphometric analyses of 29 cultivar-district combinations, and historical production records (2017–2021). Sixteen composite indices were developed to capture genetic diversity (Shannon-Weaver Index), productive potential, hydric vulnerability (Water Dependence and Stress Indices), economic performance, and ecological resilience. These were integrated into a novel Composite Climate Stress Impact Index (CSII) that combines system-level resilience metrics with CMIP6-derived climate projections for 2041–2070 under SSP245 and SSP585 scenarios. Results: Analysis of 29 cultivar-district combinations revealed significant spatial differentiation. Northern Khenchela exhibited higher varietal diversity (Varietal Diversity Index: 2.639 vs 0.693), superior oil conversion efficiency (0.782 vs 0.624), and greater ecological resilience (0.412 vs 0.248) than the southern zone. Cultivars Aberkane, Aimel, and Khadraia achieved the highest resilience scores (85.9–87.4%). Water stress indices were substantially higher in SKh (0.85–0.92 vs 0.52–0.68), correlating with greater production instability (coefficient of variation: 0.25 vs 0.14). CSII results highlighted that northern systems possess superior adaptive capacity under projected climate stress (+1.8 °C NKh vs +2.5 °C SKh). Conclusions: Olive system resilience in Khenchela is multi-dimensional, relying on genetic diversity, water resource management, and cultivar morphometric efficiency. Priority interventions include varietal diversification in SKh, adoption of water-efficient irrigation practices, and conservation of high-resilience cultivars. The CSII framework provides a transferable tool for assessing and prioritizing adaptation strategies in Mediterranean olive agroecosystems under climate change. Keywords: Climate resilience; Olive diversity; Composite indices; Water stress; North Africa; Adaptive capacity; CSII